METTL3-Mediated m6A RNA Methylation of ZBTB4 Interferes With Trophoblast Invasion and Maybe Involved in RSA - Huang, Nana; Gao, Yue; Zhang, Mengting; Guo, Liangjie; Qin, Litao; Liao, Shixiu; Wang, Hongdan (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) is the most abundant modification of mRNA and lncRNA in mammalian and plays an important role in many biology processes. However, whether m6A modification is associated with recurrent spontaneous abortion (RSA) and its roles still remain unclear. Methods: The Immunoprecipitation Sequencing (MeRIP-Seq) was used to study the global m6A modification pattern in RSAs and Controls. RNA Sequencing (RNA-Seq) was used to study the level of global mRNA in two groups. Real Time Quantitative PCR (RT-qPCR) was used to verify the level of mRNA of METTL3 and ZBTB4. MeRIP–qPCR was conducted to test the level of ZBTB4 m6A modification in two groups. In order to further explore whether ZBTB4 was the substrate of METTL3 the HTR-8/SVneo (HTR-8) cell line was selected for knockdown and overexpression of METTL3. To study whether METTL3 regulated ZBTB4 expression by recognizing ZBTB4 mRNA m6A motifs in Coding Sequences (CDS), Dual-Luciferase Reporter Assay was conducted. RNA stability assays using Actinomycin D was conducted to study the RNA stability of the HTR-8 cell line with METTL3 overexpression and knockdown. To illustrate the role of METTL3 in the invasion of trophoblast, matrigel invasion assays and transwell migration assays were conducted using HTR-8 cell line with METTL3 overexpression and knockdown. Results: A total of 65 genes were found with significant differences both in m6A modification and mRNA expression. We found m6A methyltransferase METTL3 were significantly down-regulated in RSA group. Through gene function analysis, RT-qPCR, MeRIP–qPCR validation experiment, knockdown and overexpression of METTL3 in HTR-8 cell line, ZBTB4 was selected as one of targets of METTL3. Furthermore, we clarified that METTL3 regulated the expression of ZBTB4 by recognizing ZBTB4 mRNA m6A Motifs in the CDS by Dual-Luciferase Reporter Assay, and METTL3 regulated the invasion of trophoblast by altering the stability and expression of ZBTB4 by RNA stability, matrigel invasion and Transwell migration assays. Conclusions: Our study revealed the mechanism by which METTL3 regulated the stability and expression of ZBTB4 and the trophoblast migration ability of RSA. A new perspective was provided for exploring the mechanism of embryonic development in RSA patients.